REPRODUCTIVE PERFORMANCE OF ZEBRAFISH (Danio rerio) AFTER EXPOSURE OF BENENG TARO LEAF EXTRACT - Dani Kusuma; Muh. Herjayanto; Saifullah Saifullah; Mohamad Ana Syabana Amin (Media Akuakultur, 2026)
Beneng taro leaves (Xanthosoma undipes) have potential benefits for fish, including reproductive performance, but their use has not been widely studied. Therefore, research on the effect of Beneng taro leaf extract on zebrafish (Danio rerio) reproduction is crucial as basis for use in aquaculture. This study aimed to analyze the reproductive performance of zebrafish after exposure to Beneng taro leaf extract solution. The reproductive performance parameters observed were egg number, egg morphometry, egg fertilization rate, and egg hatching rate. The research method used was an experiment with a Completely Randomized Design (CRD). Sublethal dose tests were conducted at concentrations of 250 - 450 ppm for 96 hours. Reproductive performance tests used a concentration of 350 ppm with exposure durations of 0, 24, 48, and 96 hours. The results showed that exposure to a sublethal concentration of 350 ppm did not affect zebrafish reproductive performance. Based on statistics, each treatment did not show significant differences. The average number of eggs in each treatment was not much different, namely 43±8-46±5, the fertilization rate was around 45 ± 2 – 50 ± 14%, and the hatching rate was around 44 ± 4 – 47 ± 8%. In egg morphometry, the egg diameter ranged from 1.15 ± 0.03 - 1.20 ± 0.02 mm and the yolk volume was 0.084 ± 0.003 - 0.184 ± 0.020 mm3.